Effect of arsenic on reflectance spectra and chlorophyll fluorescence of aquatic plants - Iriel, Analia (2015)
Arsenic pollution of groundwater is a serious problem in many regions of Latin America that causes severe risks to human health. As a consequence, non-destructive monitoring methodologies, sensitive to arsenic presence in the environment and able to perform a rapid screening of large polluted areas, are highly sought-after. Both chlorophyll – a fluorescence and reflectance of aquatic plants may be potential indicators to sense toxicity in water media. In this work, the effects of arsenic on the optical and photophysical properties of leaves of different aquatic plants (Vallisneria gigantea, Azolla filiculoides and Lemna minor) were evaluated. Reflectance spectra were recorded for the plant leaves from 300 to 2400 nm. The spectral distribution of the fluorescence was also studied and corrected for light re-absorption processes. Photosynthetic parameters (Fv/Fm and ΦPSII) were additionally calculated from the variable chlorophyll fluorescence recorded with a pulse amplitude modulated fluorometer. Fluorescence and reflectance properties for V. gigantea and A. filiculoides were sensitive to arsenic presence in contrast to the behaviour of L. minor. Observed changes in fluorescence spectra could be interpreted in terms of preferential damage in photosystem II. The quantum efficiency of photosystem II for the first two species was also affected, decreasing upon arsenic treatment. As a result of this research, V. gigantea and A. filiculoides were proposed as bioindicators of arsenic occurrence in aquatic media.